2020
DOI: 10.1002/ejp.1555
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain measured with the modified Bernese Pain Scale for Neonates is influenced by individual contextual factors

Abstract: Background Individual contextual factors like gestational age (GA) or previous painful experiences have an influence on neonates’ pain responses and may lead to inaccurate pain assessment when not appropriately considered. Objectives We set out to determine the influence of individual contextual factors on variability in pain response in neonates, measured with the modified Bernese Pain Scale for Neonates (BPSN), and, if necessary, to incorporate relevant individual factors into a revised version of the BPSN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Therefore, it can only be concluded that warming as a possible additional procedure did not influence the infants' COMFORTneo score. Other elements could also influence pain evaluation, as described by Schenk et al 32 They concluded that individual contextual factors such as behavioral state, ventilation status, and postmenstrual age have an impact on the infants' pain response and recommended that clinicians incorporate this in their evaluation to achieve a more accurate clinical pain assessment of the infants. Our study did not consider this because the protocol was approved prior to the publication of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can only be concluded that warming as a possible additional procedure did not influence the infants' COMFORTneo score. Other elements could also influence pain evaluation, as described by Schenk et al 32 They concluded that individual contextual factors such as behavioral state, ventilation status, and postmenstrual age have an impact on the infants' pain response and recommended that clinicians incorporate this in their evaluation to achieve a more accurate clinical pain assessment of the infants. Our study did not consider this because the protocol was approved prior to the publication of this study.…”
Section: Discussionmentioning
confidence: 99%